Design for Experience: From Design to Business Strategy - Nakhasuwan, Sudaduang (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Due to higher productivity and innovations, design outcomes have become more and more similar in their technology, functionality, price and quality. The change towards a more human-centered design has gained popularity among many businesses. The concept is to create stronger emotional connections with customers which currently become dominant in consumer arenas. By evoking valued meanings through their products, services, and multidimensional customer experiences, companies are then able to create more value and achieve strategic advantages over their competitors. In any given case, the design is asked to influence, not just the look and feel of things, but also the quality of user experience that people have through the power of design in creating a tangible expression. As designers, we are now challenged to help companies explore and visualize directions for their future offering. This article aims to review the many definitions of experience, understanding the process of experiencing, and analyzing the role and optimizing development of experience design in marketing and business perspectives.